Perjanjian Pengikatan Jual Beli Hak atas Tanah sebagai Dasar Pembuatan Akta Jual Beli Dihadapan PPAT - Putu Arya Bagus Utama; I Nyoman Sumardika; Ni Gusti Ketut Sri Astiti (Jurnal Preferensi Hukum, 2021)
For human life, land has an important role because there is a direct relationship between humans and land. Land is the main and largest capital of Indonesia. The problems of this study are 1) Is the basis for the agreement on the sale and purchase of land rights by the parties? 2) Is PPAT authorized to make deed of sale and purchase of rights to land based on the sale and purchase agreement made by the parties? The research method used is a normative legal research method, with a literature study of primary and secondary legal materials. The results of the study can be concluded that: 1) The Agreement on the Sale and Purchase is made by the parties because the agreement that binds the seller to the buyer so as not to offer objects that are traded to other buyers, and the price of the object being traded is definitely price and there is no price increase. 2) The Land Deed Maker Officer has the authority to make the sale and purchase deed of land rights based on the sale and purchase agreement by the parties stated in article 4 paragraph 1 of Government Regulation Number 37 of 1998 concerning the Position Regulations of the Land Deed Making Officer. In this case, it is expected that the Land Deed Maker Officer in making a deed of sale and purchase in accordance with the applicable Law.